2006
DOI: 10.1093/humrep/del291
|View full text |Cite
|
Sign up to set email alerts
|

Serum anti-Mullerian hormone throughout the human menstrual cycle

Abstract: In this study, we demonstrated that serum AMH levels do not change significantly throughout the menstrual cycle. Hence, AMH exhibits a relatively stable expression during the menstrual cycle, making it an attractive determinant of ovarian activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
256
4
23

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 466 publications
(301 citation statements)
references
References 23 publications
18
256
4
23
Order By: Relevance
“…However, multiple regression analysis confirmed no correlation between AMH and FSH serum levels in each group, in agreement with previous observation in PCOS women Pigny et al 2003]. It was reported that serum AMH levels did not significantly change along with serum FSH levels that fluctuate throughout the menstrual cycle [La Marca et al 2004;La Marca et al 2006]. FSH either produced endogenously or administered did not appear to exert an effect on serum AMH levels when only one dominant follicle emerged [van Rooij et al 2002;Wachs et al 2007].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, multiple regression analysis confirmed no correlation between AMH and FSH serum levels in each group, in agreement with previous observation in PCOS women Pigny et al 2003]. It was reported that serum AMH levels did not significantly change along with serum FSH levels that fluctuate throughout the menstrual cycle [La Marca et al 2004;La Marca et al 2006]. FSH either produced endogenously or administered did not appear to exert an effect on serum AMH levels when only one dominant follicle emerged [van Rooij et al 2002;Wachs et al 2007].…”
Section: Discussionsupporting
confidence: 89%
“…It seems that the high levels of AMH observed in PCO women in the late follicular phase (day of HCG administration) is not the reason for follicular arrest (the disruption of follicular development and maturation), whereas it predicts an excessive number of small antral follicles in PCO women which were not detected by ultrasound on the day of HCG administration, compared to control women. It has been observed that serum AMH levels remain rather constant in early and late follicular phases of a natural cycle [La Marca et al 2004;La Marca et al 2006;van Houten et al 2010], indicating that serum AMH levels might not influence follicular maturation. It appears that serum AMH levels at various stages of a natural or stimulated cycle are positively correlated with the numbers of small antral follicles in the ovary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the field of reproductive medicine, extremely interesting new data on the possible clinical application of AMH measurement in the prediction of quantitative and qualitative ovarian response in ART have been published in the last few years, since AMH exhibits a relatively stable expression throughout the menstrual cycle [17]. This suggests that AMH is an attractive determinant of ovarian activity.…”
mentioning
confidence: 99%
“…This was in part derived from studies that demonstrated minimal variation of AMH levels throughout the menstrual cycle. As AMH production has declined when follicles are selected for dominance, cyclic variation is thought to be minimal enough that measurement can be performed at any timepoint in the cycle [12]. However, more recent evidence indicates that AMH levels may fluctuate more than previously thought, with higher levels in the follicular phase compared to the luteal phase [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%